498 Edmond: a feasibility study of elemental diet as an alternative to parenteral nutrition for ovarian cancer patients with inoperable malignant bowel obstruction. (4th December 2020) - Michael, Agnieszka; Allan, Lindsey; Bennett-Eastely, Kate; Herbertson, Rebecca; Skene, Simon
Abstract : Introduction/Background: Inoperable bowel obstruction (IBO) occurs in up to 50% of patients diagnosed with ovarian cancer. Nutrition support for patients with IBO is challenging. Parenteral feeding (PN) is the recommended route for patients with a prognosis of > 2 months, however there is little evidence that it improves quality of life and the cost of it is very high. If PN is not available patients are frequently discharged home from hospital with sips of clear fluids only. Management of inoperable bowel obstruction remains a major challenge and clear guidelines are needed. Elemental diet (ED) is a liquid diet that contains proteins in the form of amino acids, fats in the form of medium chain triglycerides, vitamins and trace minerals. ED is almost completely absorbed in the upper small intestine. Methodology: The primary objective of the study was to establish if ED can be used as an alternative to home PN in patients with IBO. The secondary aim was to examine the impact of ED on quality of life. The primary endpoints of the study were acceptability and tolerability of ED with respect to taste, and incidence of vomiting and pain. The secondary endpoints included the number of patients alive at the end of the study, quality of life, nutritional intake, and the number of women who can tolerate ED and subsequently be treated with palliative chemotherapy (as per standard of care). Results: 29 women with IBO caused by metastatic ovarian cancer were recruited into the EDMONd study. Of those 8 could not complete the trial due to disease progression, and 2 had missing data that was deemed irretrievable, leaving 19 patients who contributed data to the primary endpoint analysis. The mean age of the patients who continued the trial was 68 (SD 12.5). Preliminary analysis shows that 68.4% of patients met the primary endpoint and tolerated ED; the ED did not worsen the vomiting or pain as measured by Memorial Symptoms Assessment Scale. At baseline 72% of patients experienced vomiting and this number reduced to 28% by the end of week1 of the study and to 23.5% by the end of week 2. 96% of patients reported pain at baseline and this proportion reduced to 72% and 76% by the end of week 1 and 2 respectively. Conclusion: ED is well tolerated by patients with IBO and can provide an acceptable feeding option for this group of patients. Disclosures: The study was funded by Target Ovarian Cancer charity. The author received educational grants from BMS, GSK, IPSEN, NOVARTIS, PFIZER CLOVIS, TESARO, ESAI; Advisory boards: CLOVIS, ESAI, IPSEN, ROCHE, TESARO